2018
DOI: 10.1590/1807-3107bor-2018.vol32.0040
|View full text |Cite|
|
Sign up to set email alerts
|

Active compounds and derivatives of camellia sinensis responding to erosive attacks on dentin

Abstract: This research explored the potential of Camellia sinensis-derived teas and active compounds to be used as treatments to prevent dentin wear. Human root dentin slabs were randomly assigned to 5 groups (n = 10) as follows: distilled water (DW, control), epigallocatechin-3-gallate (EGCG), theaflavin gallate derivatives (TF), commercial green tea (GT), and commercial black tea (BT). The samples were submitted to a pellicle formation and an erosive cycling model (5x/day, demineralization using 0.01 M hydrochloric a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 32 publications
(45 reference statements)
0
25
0
5
Order By: Relevance
“…A carbon pencil was used to mark a horizontal small window on the cervical coronal part of each specimen. Each specimen was coated with two layers of dark color acid resistant nail varnish except for the exposed window (3×3 mm) for application of tested materials (9)(10)(11) . Baseline surface microhardness of the dentine specimen was recorded by using Vicker's microhardness tester (12,13) .…”
Section: Specimen Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…A carbon pencil was used to mark a horizontal small window on the cervical coronal part of each specimen. Each specimen was coated with two layers of dark color acid resistant nail varnish except for the exposed window (3×3 mm) for application of tested materials (9)(10)(11) . Baseline surface microhardness of the dentine specimen was recorded by using Vicker's microhardness tester (12,13) .…”
Section: Specimen Preparationmentioning
confidence: 99%
“…The specimens were randomly assigned to two equal groups (20 premolars each) as follows (A 1 ): Aloe vera (A 2 ): Chlorhexidine. Dentine specimens in each group had been soaked in a glass container filled with 100ml of each testing solutions under constant agitation at room temperature (10,17) for one minute (12,18) . The specimens were rinsed and kept in de-ionized water at 37°C for next day.…”
Section: Specimens Treatment Protocolmentioning
confidence: 99%
“…Tea protects teeth against erosive demineralization [3][4][5][6][7]9] because the chemical structure of hydroxyapatite (HA), which comprises enamel, is tolerant to substitution by different trace elements [51,52]. Reports using liquid solutions [53,54] have shown that Zn, Ca, Mg, Fe, K, and Cu, which are found in tea, are involved in tooth staining.…”
Section: Biomechanism Of Green Tea Protectionmentioning
confidence: 99%
“…Tea is one of the most popular drinks consumed worldwide, especially in China [1,2]. It has been widely reported that green tea extracts protect dental tissues [3][4][5][6]. For example, green-tea protects against dentin erosion and abrasion [3,5,7], periodontal diseases [8], and caries [9].…”
Section: Introductionmentioning
confidence: 99%
“…Green tea leaves also contain caffeine, theanine, micricetin, quercetin and kaempferol, all of which are part of the alkaloid group. The varied chemical composition of green tea has been explored in different biomedical fields, with an accent on the antioxidant, anticancer and anti-inflammatory potential of EGCG [10][11][12][13]. The EGCG structure includes a benzenediol ring attached to a tetrahydropyran fraction, a pyrogalol ring and a galloyl group (with the pyrogalol ring) [14,15].…”
Section: Introductionmentioning
confidence: 99%